BLASTOCYSTIS HOMINIS ,CRYPTOSPORIDIA ,AND STRONGYLOIDS STERCORALIS AS POTENTIALLY ONCOGENIC PARASITES IN COLORECTAL CARCINOMA (Journal of Multidisciplinary Sciences and Innovations, 2025)
Background & Aim: Colorectal cancer (CRC) is the third most commonly diagnosed cancer which has both strong environmental associations and genetic risk factors. Although some microorganisms were found to be associated with carcinogenesis in CRC, the prevalence of parasites and their association with carcinogenesis remain unclear. This study aimed to detect the prevalence and association of the parasites Blastocystis, Cryptosporidium, and Strongyloides in patients with colorectal cancer.Patients and methods: A case-control study, including 120 participants, divided into 60 patients with CRC along with 60 healthy controls. Patients were recruited from the Endemic Medicine Department Kasr Alainy Hospital, Cairo University, and Ahmed Maher Teaching Hospital. Special parasitologic testing for Blastocystis hominis,  Cryptosporidia oocysts and Strongyloides stercoralis rhbditiform larvae was done by iodine-stained smears after formol ether concentration for detection,  Modified Ziehl-neelsen staining, and  agar plate culture respectively.